2020
DOI: 10.1155/2020/1830934
|View full text |Cite
|
Sign up to set email alerts
|

Physical Training Is a Potential Modifier of Risk for Contrast-Induced Acute Kidney Injury in Diabetes Mellitus

Abstract: Background. Iodinated contrast (IC) is a leading cause of hospital-based acute kidney injury (AKI). Contrast-induced acute kidney injury (CI-AKI) is a decline in renal function due to iodinated contrast administration and occurs more frequently in individuals with increasingly common risk factors, such as diabetes mellitus (DM). Physical training (PT) can have renoprotective effects on CI-AKI in diabetic nephropathy. The aim of this study was to evaluate the injury in kidneys of diabetic rats submitted to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Every 1% decrease in HbAlc in patients with type 2 diabetes was associated with a 37% decrease in the risk of microangiopathy [20]. In patients with diabetic nephropathy, proper physical exercise may reduce the albuminuria and alleviate the progression of nephropathy [21][22]. This study showed that in patients at an early stage of T2DM nephropathy, 12 weeks of resistance training signi cantly reduced , an renal function index, and increased GFR, and the effect was more obvious than that in the control group, suggesting that resistance training may improve the renal function in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Every 1% decrease in HbAlc in patients with type 2 diabetes was associated with a 37% decrease in the risk of microangiopathy [20]. In patients with diabetic nephropathy, proper physical exercise may reduce the albuminuria and alleviate the progression of nephropathy [21][22]. This study showed that in patients at an early stage of T2DM nephropathy, 12 weeks of resistance training signi cantly reduced , an renal function index, and increased GFR, and the effect was more obvious than that in the control group, suggesting that resistance training may improve the renal function in patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…It can be said that functional food originated from the theory of dietary therapy, food nourishment, food supplement, and medicine and food homology in my country, medicine tonic is not as good as food tonic, which has been recognized by scholars all over the world [ 1 ]. Since the implementation of the functional food management measures in 1996, the state has strengthened the management and approval of functional food, stipulating functional food refers to food with specific health care functions, that is, food suitable for specific groups of people, with the ability to regulate body functions, and not for the purpose of treating diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…is was increasingly common in populations with risk factors [4]. Although all above believe that physical training is necessary, no specific experimental process is shown.…”
Section: Introductionmentioning
confidence: 99%